Secondary battery

By coating Si-containing compounds in the negative electrode with a material that expands and contracts with the active material core, the battery's internal structure is stabilized, enhancing cycle life and maintaining high energy density.

JP7619377B2Active Publication Date: 2025-01-22MURATA MFG CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022566872
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-12-02
Filing Date
2021-11-25
Publication Date
2025-01-22
Estimated Expiration
2041-11-25

AI Technical Summary

Technical Problem

Si-containing compounds in negative electrodes of secondary batteries undergo significant volume changes during charging and discharging, leading to deterioration of battery characteristics and reduced cycle life.

Method used

A secondary battery design where the surface of Si-containing compounds in the negative electrode active material is coated with a material having an elastic modulus lower than the negative electrode binder, with a tensile elongation of 100% or more and a recovery rate of 70% or more, allowing the coating to expand and contract with the active material core, thereby stabilizing the internal structure.

Benefits of technology

The design improves cycle characteristics by minimizing structural collapse of the negative electrode active material layer, maintaining high energy density while extending the battery's lifespan.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007619377000002
    Figure 0007619377000002
  • Figure 0007619377000003
    Figure 0007619377000003
  • Figure 0007619377000004
    Figure 0007619377000004
Patent Text Reader

Abstract

This secondary battery is provided with a positive electrode, a negative electrode that contains an Si-based negative electrode active material and a negative electrode binder, and an electrolyte solution; the Si-based negative electrode active material comprises an active material core that contains an Si-containing compound and a cover material that covers at least a part of the surface of the active material core; the elastic modulus of the cover material is lower than the elastic modulus of the negative electrode binder; the cover material has a tensile elongation of 100% or more; and the recovery rate of the cover material after a tensile elongation of 100% is 70% or more.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present technology relates to a secondary battery. [Background technology]

[0002] In recent years, with the spread of various electronic devices such as mobile phones, the development of secondary batteries as small, lightweight, and high-energy density power sources has been progressing. Since each component of a secondary battery affects the battery characteristics, various studies have been conducted.

[0003] For example, silicon (Si)-containing compounds are attractive intercalation materials for electrochemically active ions, and therefore have attracted attention as negative electrode active materials for secondary batteries that can realize larger battery capacities (e.g., Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2019-71227 A Summary of the Invention

[0005] However, since Si-containing compounds undergo large volume changes due to the insertion and desorption of electrochemically active ions, repeated charge and discharge can change the internal structure of the active material layer, potentially degrading the battery characteristics. Therefore, it is desirable to improve the cycle characteristics of secondary batteries that use Si-containing compounds as negative electrode active materials, even with repeated charge and discharge.

[0006] Therefore, it is desirable to provide a secondary battery capable of improving the cycle characteristics.

[0007] A secondary battery according to one embodiment of the present technology includes a positive electrode, a negative electrode containing a Si-based negative electrode active material and a negative electrode binder, and an electrolyte solution. The Si-based negative electrode active material includes an active material core containing a Si-containing compound and a coating material that coats at least a portion of the surface of the active material core. The elastic modulus of the coating material is lower than the elastic modulus of the negative electrode binder, the tensile elongation of the coating material is 100% or more, and the recovery rate of the coating material after a tensile elongation of 100% is 70% or more.

[0008] According to a secondary battery according to an embodiment of the present technology, at least a part of the surface of an active material core containing a Si-containing compound is covered with a coating material. The coating material has a modulus of elasticity lower than that of the negative electrode binder, a tensile elongation of 100% or more, and a recovery rate after a tensile elongation of 100% or more of 70%. As a result, the secondary battery according to this embodiment can suppress the collapse of the internal structure of the active material layer due to repeated charging and discharging by expanding and contracting the coating material in accordance with the expansion and contraction of the active material core containing a Si-containing compound. As a result, the secondary battery according to this embodiment can improve the cycle characteristics.

[0009] Note that the effects of the present technology are not necessarily limited to the effects described here, but may be any of a series of effects related to the present technology described below. [Brief description of the drawings]

[0010] [Figure 1] 1 is a cross-sectional view illustrating a configuration of a lithium ion secondary battery (cylindrical type) according to an embodiment of the present technology. [Diagram 2] 2 is an enlarged cross-sectional view showing the configuration of a main part of the lithium-ion secondary battery shown in FIG. [Diagram 3] FIG. 2 is a perspective view illustrating a configuration of another lithium ion secondary battery (laminate film type) according to the embodiment. [Figure 4] 4 is an enlarged view showing the configuration of a main part of the lithium ion secondary battery shown in FIG. 3. [Diagram 5] 2 is a block diagram showing a configuration of a battery pack which is an example of an application of the secondary battery according to the embodiment. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, an embodiment of the present technology will be described in detail with reference to the drawings. The description will be given in the following order. 1. Secondary battery (cylindrical type) 1-1.Configuration 1-2. Manufacturing method 1-3. Actions and Effects 2. Secondary battery (laminate film type) 2-1.Configuration 2-2. Manufacturing method 2-3. Actions and Effects 3. Uses of secondary batteries

[0012] <1. Secondary battery (cylindrical type)> First, a secondary battery according to an embodiment of the present technology will be described.

[0013] The secondary battery described here is a secondary battery that obtains battery capacity by utilizing the absorption and release of an electrode reactant, and includes a positive electrode, a negative electrode, and an electrolyte. In the secondary battery, the charge capacity of the negative electrode is larger than the discharge capacity of the positive electrode in order to prevent the electrode reactant from being deposited on the surface of the negative electrode during charging. That is, the electrochemical capacity per unit area of ​​the negative electrode is larger than the electrochemical capacity per unit area of ​​the positive electrode.

[0014] The electrode reactant is, but is not limited to, a light metal such as an alkali metal or an alkaline earth metal. The alkali metal is lithium, sodium, potassium, etc. The alkaline earth metal is beryllium, magnesium, calcium, etc.

[0015] In the following, an example will be given in which the electrode reactant is lithium. A secondary battery that obtains battery capacity by utilizing the absorption and release of lithium is a so-called lithium ion secondary battery. In a lithium ion secondary battery, lithium is absorbed and released in an ionic state.

[0016] <1-1. Configuration> Fig. 1 is a cross-sectional view showing the cross-sectional configuration of a secondary battery. Fig. 2 is an enlarged cross-sectional view showing the cross-sectional configuration of a main part (wound electrode body 20) of the secondary battery shown in Fig. 1. However, Fig. 2 shows only a part of the wound electrode body 20.

[0017] The secondary battery shown in FIG. 1 is a cylindrical lithium ion secondary battery in which a wound electrode body 20, which is a battery element, is housed inside a cylindrical battery can 11.

[0018] Specifically, the secondary battery includes a pair of insulating plates 12, 13 and a wound electrode body 20 inside a battery can 11. The wound electrode body 20 is an electrode body formed by winding a positive electrode 21 and a negative electrode 22 that are stacked on each other with a separator 23 interposed therebetween. The wound electrode body 20 is impregnated with an electrolytic solution that is a liquid electrolyte.

[0019] Battery can 11 contains one or more of iron (Fe), aluminum (Al), and alloys thereof, and has a hollow structure with one end closed and the other end open. The surface of battery can 11 may be plated with nickel (Ni), etc. Each of insulating plates 12, 13 extends in a direction intersecting the winding circumferential surface of wound electrode body 20, and is disposed opposite to each other with wound electrode body 20 sandwiched therebetween.

[0020] A battery lid 14, a safety valve mechanism 15, and a thermosensitive resistor (PTC element) 16 are crimped to the open end of the battery can 11 via a gasket 17. This causes the open end of the battery can 11 to be sealed.

[0021] The battery lid 14 includes a material similar to that of the battery can 11. The safety valve mechanism 15 and the thermosensitive resistor element 16 are provided inside the battery lid 14. The safety valve mechanism 15 is electrically connected to the battery lid 14 via the thermosensitive resistor element 16. When the internal pressure of the battery can 11 becomes equal to or higher than a certain level due to an internal short circuit or external heating, the safety valve mechanism 15 reverses the disk plate 15A to cut off the electrical connection between the battery lid 14 and the wound electrode body 20. The thermosensitive resistor element 16 is an element whose resistance increases with an increase in temperature. The thermosensitive resistor element 16 is provided to prevent abnormal heat generation due to a large current. The gasket 17 includes an insulating material. The surface of the gasket 17 may be coated with asphalt or the like.

[0022] A center pin 24 is inserted into a space provided at the center of the winding of the wound electrode body 20. However, the center pin 24 may not be provided in some cases. A positive electrode lead 25 including one or more types of conductive materials such as aluminum is connected to the positive electrode 21. The positive electrode lead 25 is electrically connected to the battery lid 14 via a safety valve mechanism 15. On the other hand, a negative electrode lead 26 including one or more types of conductive materials such as nickel is connected to the negative electrode 22. The negative electrode lead 26 is electrically connected to the battery can 11.

[0023] [Positive electrode] 2, the positive electrode 21 includes a positive electrode current collector 21A and two positive electrode active material layers 21B provided on both sides of the positive electrode current collector 21A. However, the positive electrode active material layer 21B may be provided on only one side of the positive electrode current collector 21A.

[0024] (Positive electrode current collector) The positive electrode current collector 21A includes one or more of conductive materials such as aluminum, nickel, stainless steel, etc. The positive electrode current collector 21A may be provided in a single layer or in a multi-layer structure.

[0025] (Cathode active material layer) The positive electrode active material layer 21B contains, as a positive electrode active material, any one or more types of positive electrode materials capable of absorbing and releasing lithium. However, the positive electrode active material layer 21B may further contain any one or more types of other materials such as a positive electrode binder and a positive electrode conductive agent.

[0026] The positive electrode material is a lithium-containing compound that can provide a high energy density. The type of the lithium-containing compound is not particularly limited, but examples thereof include a lithium-containing composite oxide and a lithium-containing phosphate compound.

[0027] The lithium-containing composite oxide is an oxide having a crystal structure of either a layered rock salt type or a spinel type, etc., and containing lithium and one or more other elements as constituent elements. The lithium-containing phosphate compound is a phosphate compound having a crystal structure of, for example, an olivine type, and containing lithium and one or more other elements as constituent elements.

[0028] The other element in the above means an element other than lithium. The type of the other element is not particularly limited as long as it is one or more of any elements. Specifically, in order to obtain a higher voltage, the other element is preferably an element belonging to Groups 2 to 15 of the long periodic table. More specifically, the other element is more preferably nickel (Ni), cobalt (Co), manganese (Mn), iron (Fe), or the like.

[0029] The lithium-containing composite oxide having a layered rock-salt type crystal structure is, for example, a compound represented by each of the following formulas (1) to (3).

[0030] Li a Mn (1-b-c) Ni b M1 c O (2-d) F e (1) (M1 is at least one of cobalt (Co), magnesium (Mg), aluminum (Al), boron (B), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), zinc (Zn), zirconium (Zr), molybdenum (Mo), tin (Sn), calcium (Ca), strontium (Sr), and tungsten (W). a to e satisfy 0.8 ≤ a ≤ 1.2, 0 < b < 0.5, 0 ≤ c ≤ 0.5, (b + c) < 1, -0.1 ≤ d ≤ 0.2, and 0 ≤ e ≤ 0.1. However, the composition of lithium varies depending on the charge-discharge state, and a is the value in the fully discharged state.)

[0031] Li a Ni (1-b) M2 b O (2-c) F d ···(2) (M2 is at least one of cobalt (Co), manganese (Mn), magnesium (Mg), aluminum (Al), boron (B), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), zinc (Zn), molybdenum (Mo), tin (Sn), calcium (Ca), strontium (Sr), and tungsten (W). a to d satisfy 0.8 ≤ a ≤ 1.2, 0.005 ≤ b ≤ 0.5, -0.1 ≤ c ≤ 0.2, and 0 ≤ d ≤ 0.1. However, the composition of lithium varies depending on the charge-discharge state, and a is the value in the fully discharged state.)

[0032] Li a Co (1-b) M3 b O (2-c) F d ···(3) (M3 is at least one of nickel (Ni), manganese (Mn), magnesium (Mg), aluminum (Al), boron (B), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), zinc (Zn), molybdenum (Mo), tin (Sn), calcium (Ca), strontium (Sr), and tungsten (W). a to d satisfy 0.8≦a≦1.2, 0≦b<0.5, -0.1≦c≦0.2, and 0≦d≦0.1. However, the composition of lithium varies depending on the charge / discharge state, and a is the value in a fully discharged state.)

[0033] Specific examples of lithium-containing composite oxides having a layered rock-salt crystal structure are LiNiO2, LiCoO2, and LiCo 0.98 Al0 0.01 Mg 0.01 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.8 Co 0.15 Al 0.05 O2, LiNi 0.33 Co 0.33 Mn 0.33 O2, Li 1.2 Mn 0.52 Co 0.175 Ni 0.1 O2 and Li 1.15 (M 0.65 Ni 0.22 Co 0.13 )O2, etc.

[0034] In addition, when the lithium-containing composite oxide having a layered rock-salt type crystal structure contains nickel (Ni), cobalt (Co), manganese (Mn) and aluminum (Al) as constituent elements, in order to obtain a high energy density, the atomic ratio of nickel (Ni) is preferably 50 atomic % or more.

[0035] The lithium-containing composite oxide having a spinel-type crystal structure is, for example, a compound represented by the following formula (4).

[0036] Li a Mn (2-b) M4b O c F d (4) (M4 is at least one of cobalt (Co), nickel (Ni), magnesium (Mg), aluminum (Al), boron (B), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), zinc (Zn), molybdenum (Mo), tin (Sn), calcium (Ca), strontium (Sr), and tungsten (W). a to d satisfy 0.9≦a≦1.1, 0≦b≦0.6, 3.7≦c≦4.1, and 0≦d≦0.1. However, the composition of lithium varies depending on the charge / discharge state, and a is the value in a fully discharged state.)

[0037] A specific example of the lithium-containing composite oxide having a spinel type crystal structure is LiMn2O4.

[0038] The lithium-containing phosphate compound having an olivine type crystal structure is, for example, a compound represented by the following formula (5).

[0039] Li a M5PO4···(5) (M5 is at least one of cobalt (Co), manganese (Mn), iron (Fe), nickel (Ni), magnesium (Mg), aluminum (Al), boron (B), titanium (Ti), vanadium (V), niobium (Nb), copper (Cu), zinc (Zn), molybdenum (Mo), calcium (Ca), strontium (Sr), tungsten (W) and zirconium (Zr). a satisfies 0.9≦a≦1.1. However, the composition of lithium varies depending on the charge / discharge state, and a is the value in a fully discharged state.)

[0040] Specific examples of lithium-containing phosphate compounds having an olivine crystal structure include LiFePO4, LiMnPO4, and LiFe 0.5 Mn 0.5 PO4 and LiFe 0.3 Mn 0.7 PO4, etc.

[0041] The lithium-containing composite oxide may be a compound represented by the following formula (6).

[0042] (Li2MnO3) x (LiMnO2) (1-x) (6) (x satisfies 0≦x≦1. However, the lithium composition varies depending on the charge / discharge state, and x is the value in a fully discharged state.)

[0043] In addition, the positive electrode material may be an oxide, a disulfide, a chalcogenide, or a conductive polymer. The oxide is titanium oxide, vanadium oxide, or manganese dioxide. The disulfide is titanium disulfide or molybdenum sulfide. The chalcogenide is niobium selenide. The conductive polymer is sulfur, polyaniline, or polythiophene.

[0044] The positive electrode binder includes one or more of synthetic rubbers and polymeric compounds. The synthetic rubbers include styrene-butadiene rubbers, fluorine-based rubbers, and ethylene-propylene-diene rubbers. The polymeric compounds include polyvinylidene fluoride and polyimide.

[0045] The positive electrode conductive agent includes one or more conductive materials such as carbon materials. Carbon materials include graphite, carbon black, acetylene black, and ketjen black. However, the positive electrode conductive agent may be a metal material or a conductive polymer, etc., as long as it is a conductive material.

[0046] [Negative electrode] 2, the negative electrode 22 includes a negative electrode current collector 22A and two negative electrode active material layers 22B provided on both sides of the negative electrode current collector 22A. However, the negative electrode active material layer 22B may be provided on only one side of the negative electrode current collector 22A. Here, the chargeable capacity of the negative electrode 22 is preferably larger than the discharge capacity of the positive electrode 21 in order to prevent unintentional deposition of lithium metal on the surface of the negative electrode 22 during charging. That is, the electrochemical equivalent of the negative electrode 22 is preferably larger than the electrochemical equivalent of the positive electrode 21.

[0047] (Negative electrode current collector) The negative electrode current collector 22A includes one or more of conductive materials such as copper, aluminum, nickel, stainless steel, etc. The negative electrode current collector 22A may be provided in a single layer or in a multi-layer structure.

[0048] The surface of the negative electrode current collector 22A is preferably roughened by electrolysis or the like, so that the negative electrode current collector 22A can improve the adhesion to the negative electrode active material layer 22B by utilizing the so-called anchor effect.

[0049] (Negative electrode active material layer) The negative electrode active material layer 22B includes a Si-based negative electrode active material including an active material core and a coating material, and a negative electrode binder.

[0050] The active material core is the center portion of a primary particle of the Si-based negative electrode active material, and contains one or more types of Si-containing compounds capable of absorbing lithium and releasing lithium.

[0051] The Si-containing compound has excellent lithium absorption and release capabilities, and therefore can obtain a remarkably high energy density. The Si-containing compound may be a simple substance of silicon, a silicon alloy, a silicon compound, or a material containing one or more of these phases. The "simple substance" described here means a general simple substance and may contain a trace amount of impurities. In other words, the purity of the simple substance is not necessarily limited to 100%.

[0052] The silicon alloy contains, as constituent elements other than silicon, any one or more metal elements among tin (Sn), nickel (Ni), copper (Cu), iron (Fe), cobalt (Co), manganese (Mn), zinc (Zn), indium (In), silver (Ag), titanium (Ti), germanium (Ge), bismuth (Bi), antimony (Sb), and chromium (Cr). The silicon compound contains any one or more of carbon (C) and oxygen (O) as constituent elements other than silicon. At this time, carbon (C) may be contained on the surface of the silicon particles. Note that the silicon compound may contain any one or more of the series of metal elements described for the silicon alloy as constituent elements other than silicon.

[0053] The silicon alloy and the silicon compound are SiB4, SiB6, Mg2Si, Ni2Si, TiSi2, MoSi2, CoSi2, NiSi2, CaSi2, CrSi2, Cu5Si, FeSi2, MnSi2, NbSi2, TaSi2, VSi2, WSi2, ZnSi2, SiC, Si3N4, Si2N2O, SiO v (0 < v ≤ 2), and LiSiO, etc. Note that the range of v may also be more than 0.2 and less than 1.4.

[0054] The coating material covers at least a part of the surface of the active material core and contains an organic resin having a tensile elongation of 100% or more and a recovery rate after a tensile elongation of 100% of 70% or more.

[0055] The fact that the tensile elongation is 100% or more means that in a tensile test using a dumbbell-shaped test piece conforming to JIS6251, the test piece can be extended until the amount of elongation becomes 100% or more of the length before the test. For example, the fact that the tensile elongation is 100% or more means that a test piece (dumbbell shape No. 8) with a length of 16 mm can be pulled and extended to a length of 32 mm or more.

[0056] The recovery rate of 70% or more after 100% tensile elongation means that in a tensile test using a dumbbell-shaped test piece conforming to JIS 6251, after the test piece is stretched to 100% of the length before the test, the test piece shrinks to less than 30% of the length before the test (i.e., the shrinkage amount of the test piece is 70% or more of the length before the test). For example, the recovery rate of 70% or more after 100% tensile elongation means that when a 16 mm long test piece (dumbbell-shaped No. 8) is pulled to a length of 32 mm or more and then stopped, the test piece shrinks to a length of less than 20.8 mm.

[0057] The coating material can reduce the active sites between the active material core and the electrolyte by coating at least a part of the surface of the active material core containing the Si-containing compound, thereby improving the cycle characteristics of the secondary battery by suppressing side reactions of the electrolyte during charging and discharging.

[0058] Moreover, the covering material contains an organic resin having a tensile elongation of 100% or more and a small elongation strain with a recovery rate of 70% or more after a tensile elongation of 100%, so that the covering material can expand and contract in accordance with the expansion and contraction of the active material core during charging and discharging. Specifically, the covering material contains an organic resin having a high tensile elongation and a high recovery rate after a tensile elongation of 100%, so that the negative electrode active material layer 22B can return to its original state when the active material core contracts after expansion. Therefore, the covering material can suppress the negative electrode active material layer 22B from gradually expanding as the charging and discharging cycles proceed, and the contact between the Si-based negative electrode active materials from decreasing. According to this, the covering material can suppress the internal structure of the negative electrode active material layer 22B from collapsing due to the expansion and contraction while maintaining the minimum expansion and contraction of the negative electrode active material layer 22B. Therefore, the covering material can improve the cycle characteristics of the secondary battery by suppressing the deterioration of the structure of the negative electrode active material layer 22B during charging and discharging.

[0059] An example of such an organic resin with a small elongation strain is a polyurethane resin, which is a polymer of a polyolefin polyol and a polyisocyanate, and has an average molecular weight of 10,000 or less. However, the organic resin contained in the coating material is not limited to the above polyurethane resin. The organic resin contained in the coating material may be another organic resin as long as it has a tensile elongation of 100% or more and a recovery rate of 70% or more after a tensile elongation of 100%.

[0060] At least a part of the surface of the active material core may be further coated with a surface conductive agent containing one or more conductive materials such as carbon materials. The surface conductive agent can more firmly connect the primary particles of the Si-based negative electrode active material or the secondary particles of the Si-based negative electrode active material, and therefore can suppress the collapse of the conductive network of the Si-based negative electrode active material due to the expansion and contraction of the active material core. As a result, the surface conductive agent can more firmly maintain the conductive network formed inside the negative electrode active material layer 22B, and therefore the cycle characteristics of the secondary battery can be improved.

[0061] The surface conductive agent can also reduce the electrical resistance of the Si-based negative electrode active material, which is increased by the coating of the coating material, and can also reduce the electrical resistance of the primary particles of the granulated Si-based negative electrode active material. Thus, the surface conductive agent can suppress the deterioration of the cycle characteristics of the secondary battery caused by the increase in the electrical resistance of the Si-based negative electrode active material.

[0062] Examples of the surface conductive agent include carbon materials such as carbon black, flake graphite, and carbon nanotubes. The surface conductive agent is preferably a carbon nanotube, and more preferably a carbon nanotube having a smaller tube diameter. This is because when the surface conductive agent is a carbon nanotube, the smaller tube diameter of the carbon nanotube allows the same effect to be obtained even with a smaller amount of the surface conductive agent added.

[0063] The negative electrode binder includes one or more of polymer compounds and synthetic rubbers having a higher elastic modulus than the coating material that coats the active material core of the Si-based negative electrode active material. The negative electrode binder includes polymer compounds and synthetic rubbers having a higher elastic modulus than the coating material, thereby suppressing the amount of expansion of the negative electrode active material layer 22B as a whole, thereby improving the cycle characteristics of the secondary battery. For example, when the coating material is a polyurethane resin having an average molecular weight of 10,000 or less obtained by polymerizing a polyolefin polyol and a polyisocyanate, the negative electrode binder preferably includes polyvinylidene fluoride, polyacrylate (such as sodium polyacrylate or lithium polyacrylate), polyimide, aramid, polyacrylamide, and styrene butadiene rubber.

[0064] Furthermore, for reasons described below, the negative electrode active material layer 22B may contain a carbon-based negative electrode active material containing a carbon material, in addition to the Si-based negative electrode active material.

[0065] Carbon material is a general term for materials containing carbon as a constituent element. The crystal structure of carbon material hardly changes during absorption and release of lithium, so that it is possible to stably obtain a high energy density. In addition, carbon material also functions as a negative electrode conductive agent, so that it is possible to improve the conductivity of the negative electrode active material layer 22B.

[0066] The carbon material may be graphitizable carbon, non-graphitizable carbon, artificial graphite, natural graphite, etc. However, the interplanar spacing of the (002) plane of non-graphitizable carbon is preferably 0.37 nm or more. Also, the interplanar spacing of the (002) plane of artificial graphite and natural graphite is preferably 0.34 nm or less.

[0067] More specifically, the carbon material includes pyrolytic carbon, cokes, glassy carbon fiber, organic polymer compound calcined body, activated carbon, and carbon black. The cokes include pitch coke, needle coke, and petroleum coke. The organic polymer compound calcined body is a calcined product obtained by calcining (carbonizing) a polymer compound such as a phenolic resin and a furan resin at an appropriate temperature. The carbon material may be low-crystalline carbon heat-treated at a temperature of about 1000° C. or less, or may be amorphous carbon. The shape of the carbon material may be any of fibrous, spherical, granular, and scaly shapes.

[0068] Metallic materials such as Si-containing compounds have the advantage of having a high theoretical capacity, but tend to expand and contract vigorously during charging and discharging. On the other hand, carbon materials have a low theoretical capacity, but tend not to expand or contract during charging and discharging. Therefore, by using a carbon material and a metallic material in combination, it is possible to obtain a high theoretical capacity (i.e., battery capacity) while suppressing the expansion and contraction of the negative electrode active material layer 22B during charging and discharging.

[0069] That is, it is preferable that the negative electrode active material layer 22B contains both a Si-based negative electrode active material and a carbon-based negative electrode active material. In this case, the secondary battery can achieve a higher theoretical capacity while further suppressing the expansion and contraction of the negative electrode active material layer 22B during charging and discharging.

[0070] The negative electrode active material layer 22B may further contain other materials such as a negative electrode conductive agent, similar to the positive electrode active material layer 21B. The negative electrode conductive agent, like the above-mentioned positive electrode conductive agent, contains one or more conductive materials such as carbon materials. Examples of carbon materials include graphite, carbon black, acetylene black, and ketjen black. However, the negative electrode conductive agent may be a metal material, a conductive polymer, or the like, so long as it is a conductive material.

[0071] [Separator] As shown in FIG. 2, separator 23 is interposed between positive electrode 21 and negative electrode 22, and prevents a short circuit caused by contact between positive electrode 21 and negative electrode 22 while allowing lithium ions to pass through.

[0072] The separator 23 includes one or more types of porous films such as synthetic resins and ceramics. The separator 23 may be a laminated film in which two or more types of porous films are laminated on each other. The synthetic resins include polytetrafluoroethylene, polypropylene, and polyethylene.

[0073] The separator 23 may include the porous film (substrate layer) and a polymer compound layer provided on one or both sides of the substrate layer. This allows the separator 23 to improve adhesion to each of the positive electrode 21 and the negative electrode 22, making the wound electrode body 20 less likely to be distorted. By making the wound electrode body 20 less likely to be distorted, the decomposition reaction of the electrolyte is suppressed and leakage of the electrolyte impregnated in the substrate layer is also suppressed, making it possible to suppress an increase in resistance and swelling of the secondary battery when it is repeatedly charged and discharged.

[0074] The polymer compound layer contains one or more types of polymer compounds such as polyvinylidene fluoride, which has excellent physical strength and is electrochemically stable. The polymer compound layer may contain one or more types of insulating particles such as inorganic particles to improve safety. The type of inorganic particles is not particularly limited, but may be aluminum oxide, aluminum nitride, or the like.

[0075] [Electrolyte] The electrolyte contains a solvent, an electrolyte salt, and the like, and as described above, is impregnated into the wound electrode body 20. That is, the electrolyte is impregnated into the separator 23, and also into each of the positive electrode 21 and the negative electrode 22.

[0076] (solvent) The solvent contains one or more kinds of non-aqueous solvents (organic solvents). An electrolyte solution containing a non-aqueous solvent is a so-called non-aqueous electrolyte solution.

[0077] The non-aqueous solvent is a cyclic carbonate ester, a chain carbonate ester, a chain carboxylate ester, a lactone, or a nitrile (mononitrile) compound, which allows the secondary battery to have excellent battery capacity, cycle characteristics, storage characteristics, and the like.

[0078] Cyclic carbonates include ethylene carbonate, propylene carbonate, and butylene carbonate. Linear carbonates include dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and methyl propyl carbonate. Lactones include γ-butyrolactone and γ-valerolactone. Linear carboxylates include methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, methyl isobutyrate, methyl trimethylacetate, and ethyl trimethylacetate. Nitriles include acetonitrile, methoxyacetonitrile, and 3-methoxypropionitrile.

[0079] Other examples of the solvent include 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, tetrahydropyran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 1,3-dioxane, 1,4-dioxane, N,N-dimethylformamide, N-methylpyrrolidinone, N-methyloxazolidinone, N,N'-dimethylimidazolidinone, nitromethane, nitroethane, sulfolane, trimethyl phosphate, and dimethyl sulfoxide. Even when these solvents are used, the secondary battery can obtain the same advantages.

[0080] In particular, in order to obtain better battery capacity, cycle characteristics, and storage characteristics, it is preferable that the solvent contains one or more of carbonates such as ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.

[0081] In such a case, it is more preferable that the solvent contains a combination of a cyclic carbonate ester such as ethylene carbonate and propylene carbonate, which are high viscosity (high dielectric constant) solvents (relative dielectric constant ε≧30), and a chain carbonate ester such as dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate, which are low viscosity solvents (viscosity≦1 mPa s).This allows the solvent to improve the dissociation of the electrolyte salt and the mobility of the ions.

[0082] The solvent may also contain an unsaturated cyclic carbonate, a halogenated carbonate, a sulfonate, an acid anhydride, a dinitrile compound, a diisocyanate compound, etc. In such a case, the solvent can improve the chemical stability of the electrolyte solution, and therefore can suppress decomposition reactions of the electrolyte solution, etc.

[0083] The unsaturated cyclic carbonate is a cyclic carbonate having one or more unsaturated bonds (carbon-carbon double bonds). Specifically, the unsaturated cyclic carbonate is vinylene carbonate (1,3-dioxol-2-one), vinylethylene carbonate (4-vinyl-1,3-dioxolane-2-one), methyleneethylene carbonate (4-methylene-1,3-dioxolane-2-one), etc. The content of the unsaturated cyclic carbonate in the solvent is not particularly limited, but may be 0.01% by mass to 10% by mass.

[0084] The halogenated carbonate is a cyclic or chain-like carbonate containing one or more halogens as a constituent element. The type of halogen is not particularly limited, but may be one or more of fluorine, chlorine, bromine, iodine, etc. Specifically, the cyclic halogenated carbonate is 4-fluoro-1,3-dioxolan-2-one, 4,5-difluoro-1,3-dioxolan-2-one, etc. Specifically, the chain-like halogenated carbonate is fluoromethyl methyl carbonate, bis(fluoromethyl) carbonate, difluoromethyl methyl carbonate, etc. The content of the halogenated carbonate in the solvent is not particularly limited, but may be 0.01% by mass to 50% by mass.

[0085] The sulfonate ester may be a monosulfonate ester or a disulfonate ester. The monosulfonate ester may be a cyclic monosulfonate ester or a chain monosulfonate ester. Specifically, the cyclic monosulfonate ester is a sultone such as 1,3-propane sultone and 1,3-propene sultone. The chain monosulfonate ester is a compound in which a cyclic monosulfonate ester is cut midway. The disulfonate ester may be a cyclic disulfonate ester or a chain disulfonate ester. The content of the sulfonate ester in the solvent is not particularly limited, but may be 0.5% by mass to 5% by mass.

[0086] The acid anhydride includes carboxylic acid anhydride, disulfonic acid anhydride, and carboxylic acid sulfonic acid anhydride. Specifically, the carboxylic acid anhydride includes succinic acid anhydride, glutaric acid anhydride, and maleic acid anhydride. The disulfonic acid anhydride includes ethane disulfonic acid anhydride and propane disulfonic acid anhydride. The carboxylic acid sulfonic acid anhydride includes sulfobenzoic acid anhydride, sulfopropionic acid anhydride, and sulfobutyric acid anhydride. The content of the acid anhydride in the solvent is not particularly limited, but may be 0.5% by mass to 5% by mass.

[0087] Dinitrile compounds are NC-C m H 2m It is a compound represented by the formula -CN (m is an integer of 1 or more). Specifically, the dinitrile compound is succinonitrile (NC-C2H4-CN), glutaronitrile (NC-C3H6-CN), adiponitrile (NC-C4H8-CN), phthalonitrile (NC-C6H4-CN), etc. The content of the dinitrile compound in the solvent is not particularly limited, but may be 0.5% by mass to 5% by mass.

[0088] The diisocyanate compound is OCN-C n H 2n -NCO (n is an integer of 1 or more). Specifically, the diisocyanate compound is OCN-CH 12--NCO, etc. The content of the diisocyanate compound in the solvent is not particularly limited, but may be 0.5% by mass to 5% by mass.

[0089] The electrolyte salt includes one or more kinds of lithium salts. However, the electrolyte salt may include a salt other than the lithium salt. The salt other than the lithium salt may be a salt of a light metal other than lithium.

[0090] The lithium salts include lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium tetraphenylborate (LiB(C6H5)4), lithium methanesulfonate (LiCH3SO3), lithium trifluoromethanesulfonate (LiCF3SO3), lithium tetrachloroaluminate (LiAlCl4), dilithium hexafluorosilicate (Li2SiF6), lithium chloride (LiCl), and lithium bromide (LiBr). When these lithium salts are used, the secondary battery can have excellent battery capacity, cycle characteristics, and storage characteristics.

[0091] In particular, the electrolyte salt preferably contains one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, and lithium hexafluoroarsenate, and more preferably contains lithium hexafluorophosphate. In such a case, the electrolyte salt can reduce the internal resistance, thereby further improving the battery characteristics of the secondary battery.

[0092] The content of the electrolyte salt is not particularly limited, but in order to obtain high ion conductivity, the content of the electrolyte salt is preferably 0.3 mol / kg to 3.0 mol / kg relative to the solvent.

[0093] The secondary battery according to this embodiment can perform charge and discharge operations as follows.

[0094] Specifically, during charging, the secondary battery releases lithium ions from the positive electrode 21 and absorbs lithium ions into the negative electrode 22 via the electrolyte. On the other hand, during discharging, the secondary battery releases lithium ions from the negative electrode 22 and absorbs lithium ions into the positive electrode 21 via the electrolyte. This allows the secondary battery to repeatedly perform charge and discharge operations.

[0095] <1-2. Manufacturing method> The secondary battery according to this embodiment can be manufactured by the following procedure. Specifically, after the positive electrode 21 and the negative electrode 22 are manufactured, the lithium ion secondary battery is assembled.

[0096] [Preparation of positive electrode] First, a positive electrode active material is mixed with a positive electrode binder and a positive electrode conductive agent, etc., as necessary, to prepare a positive electrode mixture. Then, the positive electrode mixture is dispersed or dissolved in an organic solvent, etc., to prepare a paste-like positive electrode mixture slurry. Next, the positive electrode mixture slurry is applied to both sides of the positive electrode current collector 21A, and then the positive electrode mixture slurry is dried to form the positive electrode active material layer 21B. The positive electrode active material layer 21B may be compression molded using a roll press machine, etc. At this time, the positive electrode active material layer 21B may be heated, and may be compression molded repeatedly multiple times.

[0097] [Preparation of negative electrode] The negative electrode 22 can be produced by a procedure similar to that for producing the positive electrode 21 described above.

[0098] Specifically, first, a negative electrode mixture is prepared by mixing a Si-based negative electrode active material and a negative electrode binder, and, if necessary, a carbon-based negative electrode active material and a negative electrode conductive agent. Then, the negative electrode mixture is dispersed or dissolved in an organic solvent or the like to prepare a paste-like negative electrode mixture slurry. Next, the negative electrode mixture slurry is applied to both sides of the negative electrode current collector 22A, and then the negative electrode mixture slurry is dried to form the negative electrode active material layer 22B. The negative electrode active material layer 22B may be compression molded.

[0099] [Secondary battery assembly] First, a positive electrode lead 25 is connected to the positive electrode current collector 21A by welding or the like, and a negative electrode lead 26 is similarly connected to the negative electrode current collector 22A by welding or the like. Next, the positive electrode 21 and the negative electrode 22 are stacked on top of each other via the separator 23, and then the positive electrode 21, the negative electrode 22, and the separator 23 are wound to form a wound body. Next, a center pin 24 is inserted into a space provided at the winding center of the wound body.

[0100] Next, the wound body is housed inside the battery can 11 together with the insulating plates 12, 13 so that the wound body is sandwiched between the pair of insulating plates 12, 13. At this time, the positive electrode lead 25 is connected to the safety valve mechanism 15 by welding or the like, and the negative electrode lead 26 is connected to the battery can 11 by welding or the like. Next, the electrolyte is injected into the battery can 11 to impregnate the wound body with the electrolyte. As a result, the positive electrode 21, the negative electrode 22, and the separator 23 are each impregnated with the electrolyte, and the wound electrode body 20 is formed.

[0101] Thereafter, the open end of the battery can 11 is crimped via a gasket 17, and a battery lid 14, a safety valve mechanism 15, and a thermosensitive resistor element 16 are attached to the open end of the battery can 11. In this way, the wound electrode body 20 is enclosed inside the battery can 11, and the secondary battery is completed.

[0102] <1-3. Actions and Effects> In the secondary battery described above, the coating material expands and contracts in response to the expansion and contraction of the active material core containing the Si-containing compound, so that the expansion and contraction of the negative electrode active material layer 22B can be minimized. This suppresses the deterioration of the internal structure of the negative electrode active material layer 22B, so that the secondary battery can achieve a high energy density due to the Si-containing compound while obtaining higher cycle characteristics.

[0103] <2. Secondary battery (laminate film type)> Next, a secondary battery according to another embodiment of the present disclosure will be described below, with reference to the components of the cylindrical secondary battery already described (see FIGS. 1 and 2).

[0104] Fig. 3 shows a perspective view of a laminate film type secondary battery. Fig. 4 shows a cross-sectional view of a main part (wound electrode body 30) of the secondary battery taken along line IV-IV shown in Fig. 3. However, Fig. 3 shows a state in which the wound electrode body 30 and the exterior member 40 are spaced apart from each other.

[0105] <2-1. Configuration> The secondary battery shown in FIG. 3 is a laminate film type lithium ion secondary battery in which a wound electrode body 30, which is a battery element, is housed inside a film-like exterior member 40 having flexibility (or flexibility).

[0106] The wound electrode body 30 is a wound body constructed by winding a positive electrode 33 and a negative electrode 34 that are stacked on each other with a separator 35 and an electrolyte layer 36 interposed therebetween. The wound electrode body 30 is protected by a protective tape 37. The electrolyte layer 36 is interposed between the positive electrode 33 and the separator 35, and is also interposed between the negative electrode 34 and the separator 35.

[0107] A positive electrode lead 31 is connected to the positive electrode 33. The positive electrode lead 31 is led out from the inside to the outside of the exterior member 40. The positive electrode lead 31 includes one or more types of conductive materials such as aluminum, and is configured in any one of a thin plate shape, a mesh shape, and the like.

[0108] A negative electrode lead 32 is connected to the negative electrode 34. The negative electrode lead 32 is led out from the inside to the outside of the exterior member 40 in the same direction as the positive electrode lead 31. The negative electrode lead 32 includes one or more types of conductive materials such as copper, nickel, and stainless steel, and is configured in the same shape as the positive electrode lead 31.

[0109] The exterior member 40 is a sheet of film that can be folded in the direction of the arrow R shown in Fig. 3. A recess 40U for accommodating the wound electrode body 30 is provided in a part of the exterior member 40.

[0110] The exterior member 40 is a laminate (laminate film) in which a fusion layer, a metal layer, and a surface protection layer are laminated in this order. The secondary battery is constructed by folding the exterior member 40 so that the fusion layers face each other via the wound electrode body 30, and then fusing the outer peripheral edges of the fusion layers together. The fusion layer is a film containing one or more types of polymer compounds such as polypropylene. The metal layer is a metal foil containing one or more types of aluminum. The surface protection layer is a film containing one or more types of polymer compounds such as nylon. The exterior member 40 may be constructed by including two of the above-mentioned laminates (laminate films) and bonding the two laminates together via an adhesive or the like.

[0111] An adhesive film 41 is inserted between the exterior member 40 and the positive electrode lead 31 to prevent the intrusion of outside air. In addition, an adhesive film 42 is inserted between the exterior member 40 and the negative electrode lead 32, similar to the adhesive film 41. Each of the adhesive films 41 and 42 contains a material having adhesiveness to each of the positive electrode lead 31 and the negative electrode lead 32. Specifically, each of the adhesive films 41 and 42 may contain one or more types of polyolefin resins such as polyethylene, polypropylene, modified polyethylene, and modified polypropylene.

[0112] [Positive electrode, negative electrode and separator] The positive electrode 33 includes a positive electrode current collector 33A and a positive electrode active material layer 33B. The negative electrode 34 includes a negative electrode current collector 34A and a negative electrode active material layer 34B. The configurations of the positive electrode current collector 33A, the positive electrode active material layer 33B, the negative electrode current collector 34A, and the negative electrode active material layer 34B are similar to the configurations of the positive electrode current collector 21A, the positive electrode active material layer 21B, the negative electrode current collector 22A, and the negative electrode active material layer 22B. The configuration of the separator 35 is similar to the configuration of the separator 23.

[0113] [Electrolyte layer] The electrolyte layer 36 contains an electrolytic solution and a polymer compound. The electrolytic solution has the same composition as that of the electrolytic solution used in cylindrical lithium ion secondary batteries.

[0114] The electrolyte layer 36 is a so-called gel electrolyte. As a result, the electrolyte layer 36 retains the electrolyte solution in a polymer compound, thereby obtaining high ionic conductivity (approximately 1 mS / cm or more at room temperature) and preventing leakage of the electrolyte solution. The electrolyte layer 36 may further contain one or more types of other materials such as various additives.

[0115] The polymeric compound includes one or both of homopolymers and copolymers. Homopolymers include polyacrylonitrile, polyvinylidene fluoride, polytetrafluoroethylene, polyhexafluoropropylene, etc. Copolymers include copolymers of vinylidene fluoride and hexafluoropyrene, etc.

[0116] In the electrolyte layer 36, which is a gel electrolyte, the "solvent" contained in the electrolytic solution includes not only a liquid material but also a material having ion conductivity capable of dissociating the electrolyte salt. Therefore, a polymer compound having ion conductivity is also included in the above-mentioned "solvent".

[0117] The electrolyte may be used directly instead of the electrolyte layer 36. In such a case, the electrolyte is impregnated into the wound electrode body 30 (the positive electrode 33, the negative electrode 34, and the separator 35).

[0118] [Operation] A secondary battery including the electrolyte layer 36 can perform charge and discharge operations as follows. Specifically, during charging, the secondary battery releases lithium ions from the positive electrode 33 and causes the lithium ions to be absorbed in the negative electrode 34 via the electrolyte layer 36. On the other hand, during discharging, the secondary battery releases lithium ions from the negative electrode 34 and causes the lithium ions to be absorbed in the positive electrode 33 via the electrolyte layer 36. This allows the secondary battery to repeatedly perform charge and discharge operations.

[0119] <2-2. Manufacturing method> A secondary battery including the electrolyte layer 36 can be manufactured by any of the following three procedures.

[0120] [Step 1] First, the positive electrode 33 and the negative electrode 34 are fabricated by the same procedures as those for fabricating the positive electrode 21 and the negative electrode 22 described above. Specifically, the positive electrode 33 is formed by forming a positive electrode active material layer 33B on both sides of a positive electrode current collector 33A. In addition, the negative electrode 34 is formed by forming a negative electrode active material layer 34B on both sides of a negative electrode current collector 34A.

[0121] Next, a precursor solution is prepared by mixing an electrolytic solution, a polymer compound, an organic solvent, etc. Then, the precursor solution is applied to the positive electrode 33, and the precursor solution is dried to form the electrolyte layer 36. Similarly, the precursor solution is applied to the negative electrode 34, and the precursor solution is dried to form the electrolyte layer 36.

[0122] Thereafter, the positive electrode lead 31 is connected to the positive electrode current collector 33A by welding or the like. Similarly, the negative electrode lead 32 is connected to the negative electrode current collector 34A by welding or the like. Next, the positive electrode 33 and the negative electrode 34 are laminated together via the separator 35, and then the positive electrode 33, the negative electrode 34, and the separator 35 are wound to form the wound electrode body 30. Next, a protective tape 37 is attached to the surface of the wound electrode body 30.

[0123] Furthermore, after folding the exterior member 40 so as to sandwich the wound electrode body 30, the outer peripheral edges of the exterior member 40 are bonded together using a heat fusion method or the like. At this time, an adhesive film 41 is inserted between the positive electrode lead 31 and the exterior member 40, and an adhesive film 42 is inserted between the negative electrode lead 32 and the exterior member 40. This completes a laminate film type secondary battery in which the wound electrode body 30 is enclosed inside the exterior member 40.

[0124] [Second Step] First, the positive electrode 33 and the negative electrode 34 are prepared, and then the positive electrode lead 31 is connected to the positive electrode 33, and the negative electrode lead 32 is connected to the negative electrode 34. Next, the positive electrode 33 and the negative electrode 34 are laminated with the separator 35 interposed therebetween, and then the positive electrode 33, the negative electrode 34, and the separator 35 are wound to form a wound body. Next, a protective tape 37 is attached to the surface of the wound body. Next, the exterior member 40 is folded so as to sandwich the wound body, and then the outer peripheral edges of the remaining sides except for one side of the outer periphery of the exterior member 40 are bonded to each other by a heat fusion method or the like, thereby storing the wound body inside the bag-shaped exterior member 40.

[0125] Next, the electrolyte composition is prepared by mixing the electrolyte solution, the monomer as the raw material of the polymer compound, the polymerization initiator, and other materials such as a polymerization inhibitor as necessary. The electrolyte composition is then injected into the inside of a bag-shaped exterior member 40, and the exterior member 40 is sealed using a heat fusion method or the like. The monomer is then thermally polymerized to form a polymer compound. As a result, the electrolyte solution is held by the polymer compound, and an electrolyte layer 36 is formed. Thus, a laminate film type secondary battery in which the wound electrode body 30 is enclosed inside the exterior member 40 is completed.

[0126] [Third Step] First, a wound body is produced by the same procedure as the second procedure described above, except that a separator 35 including a base layer and a polymer compound layer formed on the base layer is used, and the wound body is stored inside a bag-shaped exterior member 40. Next, an electrolyte is injected into the interior of the exterior member 40, and the opening of the exterior member 40 is sealed using a heat fusion method or the like. Thereafter, the exterior member 40 is heated while being weighted, so that the separator 35 is adhered to each of the positive electrode 33 and the negative electrode 34 via the polymer compound layer. As a result, the polymer compound layer impregnated with the electrolyte gels, and an electrolyte layer 36 is formed. Thus, a laminate film type secondary battery in which the wound electrode body 30 is enclosed inside the exterior member 40 is completed.

[0127] In the third step, the secondary battery is less likely to swell than in the first step. Also, in the third step, the solvent and monomer (raw material of the polymer compound) are less likely to remain in the electrolyte layer 36 than in the second step, so that the polymer compound formation process is well controlled. This makes it easier for the electrolyte layer 36 to sufficiently adhere to each of the positive electrode 33, the negative electrode 34, and the separator 35.

[0128] <2-3. Actions and Effects> In the secondary battery described above, the coating material expands and contracts in response to the expansion and contraction of the active material core containing the Si-containing compound, so that the expansion and contraction of the negative electrode active material layer 22B can be minimized. This suppresses the deterioration of the internal structure of the negative electrode active material layer 22B, so that the secondary battery can achieve a high energy density due to the Si-containing compound while obtaining higher cycle characteristics.

[0129] Other functions and effects of the laminate film type secondary battery are similar to those of the cylindrical type secondary battery.

[0130] <3. Uses of secondary batteries> The use (application example) of the secondary battery is not particularly limited. The secondary battery used as a power source may be used as a main power source for electronic devices and electric vehicles, etc., or may be used as an auxiliary power source. The main power source is a power source that is used preferentially regardless of the presence or absence of other power sources, and the auxiliary power source is a power source that is used instead of the main power source or a power source that is switched from the main power source.

[0131] Specific examples of applications of secondary batteries include electronic devices such as video cameras, digital still cameras, mobile phones, notebook computers, headphone stereos, portable radios, and portable information terminals, storage devices such as backup power sources and memory cards, power tools such as electric drills and electric saws, battery packs mounted on electronic devices, medical electronic devices such as pacemakers and hearing aids, electric vehicles such as electric cars (including hybrid cars), and power storage systems such as home or industrial battery systems that store power in preparation for emergencies, etc. In these applications, one secondary battery may be used, or multiple secondary batteries may be used.

[0132] The battery pack may be configured using a single cell or a battery pack. The electric vehicle is a vehicle that operates (runs) using a secondary battery as a driving power source, and may be a hybrid vehicle that also includes a driving source other than a secondary battery. The home power storage system is capable of operating home electrical appliances and the like by utilizing power stored in a secondary battery, which is a power storage source.

[0133] Here, an example of an application of the secondary battery will be specifically described. The configuration of the application described below is merely an example and can be modified as appropriate.

[0134] Figure 5 shows the block configuration of a battery pack. The battery pack described here is a battery pack (a so-called soft pack) that uses one secondary battery, and is installed in electronic devices such as smartphones.

[0135] 5, the battery pack includes a power source 111 and a circuit board 116. The circuit board 116 is connected to the power source 111, and includes a positive terminal 125, a negative terminal 127, and a temperature detection terminal 126.

[0136] The power source 111 includes one secondary battery. In the secondary battery, a positive electrode lead 25 is connected to a positive electrode terminal 125, and a negative electrode lead 26 is connected to a negative electrode terminal 127. The power source 111 can be connected to the outside via the positive electrode terminal 125 and the negative electrode terminal 127, and can be charged and discharged via the positive electrode terminal 125 and the negative electrode terminal 127. The circuit board 116 includes a control unit 121, a switch unit 122, a PTC element 123, and a temperature detection unit 124. However, the PTC element 123 may be omitted.

[0137] The control unit 121 includes a central processing unit (CPU) and a memory, and controls the operation of the entire battery pack. The control unit 121 detects and controls the usage state of the power source 111 as necessary.

[0138] When the voltage of the power source 111 (secondary battery) reaches the overcharge detection voltage or the overdischarge detection voltage, the control unit 121 can turn off the switch unit 122 to prevent a charging current from flowing through the current path of the power source 111. The overcharge detection voltage and the overdischarge detection voltage are not particularly limited. As an example, the overcharge detection voltage is 4.2V±0.05V, and the overdischarge detection voltage is 2.4V±0.1V.

[0139] The switch unit 122 includes a charge control switch, a discharge control switch, a charge diode, a discharge diode, etc., and switches between the presence and absence of a connection between the power source 111 and an external device in response to an instruction from the control unit 121. The switch unit 122 includes a metal-oxide-semiconductor field-effect transistor (MOSFET) etc. The charge / discharge current is detected based on the ON resistance of the switch unit 122.

[0140] Temperature detection unit 124 includes a temperature detection element such as a thermistor, measures the temperature of power supply 111 using temperature detection terminal 126, and outputs the temperature measurement result to control unit 121. The temperature measurement result measured by temperature detection unit 124 is used when control unit 121 controls charging and discharging of power supply 111 in the event of abnormal heat generation, and when control unit 121 performs correction processing for the remaining capacity of power supply 111 when calculating the remaining capacity, etc. EXAMPLES

[0141] The secondary battery according to the present embodiment will be described in more detail below with reference to examples and comparative examples. Note that the examples shown below are examples for showing the feasibility and effects of the secondary battery according to the present embodiment, and the present technology is not limited to the following examples.

[0142] (Production of negative electrodes) First, 99% by mass of Si powder and 1% by mass of polyurethane resin were mixed with an appropriate amount of pure water and thoroughly stirred, and then sprayed and dried using a spray dryer to obtain Si composite secondary particles, which are Si-based negative electrode active materials. By changing conditions such as the raw materials and the mixing ratio, Si composite secondary particles (Si-based negative electrode active materials) according to each example and each comparative example were produced under the conditions shown in Table 1.

[0143] The polyurethane resin is, with some exceptions, a compound produced from a polyolefin polyol and a polyisocyanate. Specifically, the polyolefin polyol is a compound containing a hydroxyl group among polymers and copolymers of diolefins having 4 to 12 carbon atoms, and copolymers of diolefins having 4 to 12 carbon atoms and α-olefins having 2 to 22 carbon atoms. The polyisocyanate compound is one or more of aromatic polyisocyanates, aliphatic polyisocyanates, and alicyclic polyisocyanates. The average molecular weight of the polyurethane resin is 3000, 10000, or 50000. The polyurethane resin may be synthesized in advance and then mixed with Si powder, or may be mixed with Si powder together with a polymerization initiator and polymerized and synthesized by heat during drying.

[0144] Next, 10% by mass of Si composite secondary particles, 85% by mass of graphite (MesoCarbon MicroBeads: MCMB) as a carbon-based negative electrode active material, 4% by mass of a negative electrode binder, and 1% by mass of MWCNT (MultiWall Carbon NanoTube) as a negative electrode conductive agent were mixed with an appropriate amount of N-methyl-2-pyrrolidone (NMP), and kneaded and stirred in a planetary centrifugal mixer to obtain a negative electrode mixture slurry.

[0145] In addition, negative electrode mixture slurries according to each of the examples and comparative examples were produced under the conditions shown in Table 1 by changing conditions such as the raw materials and the blending ratios.

[0146] Next, the produced negative electrode mixture slurry was uniformly applied to both sides of a copper foil with a thickness of 8 μm. After the applied copper foil was dried with hot air, it was compression molded with a roll press machine to form a negative electrode sheet. Furthermore, the negative electrode sheet was cut into a strip of 72 mm x 810 mm to produce a negative electrode. Then, a negative electrode lead was attached to the exposed copper foil part of the negative electrode.

[0147] (Production of positive electrodes) A positive electrode mixture was prepared by mixing 95 mass% lithium cobalt oxide, which was a positive electrode active material, 2 mass% amorphous carbon powder (Ketjen black), and 3 mass% polyvinylidene fluoride (PVDF). The positive electrode mixture was dispersed in NMP to obtain a positive electrode mixture slurry.

[0148] Next, the positive electrode mixture slurry was uniformly applied to both sides of a strip of aluminum foil with a thickness of 10 μm. The aluminum foil after application was dried with hot air, and then compression molded with a roll press to form a positive electrode sheet. Furthermore, the positive electrode sheet was cut into a strip of 70 mm x 800 mm to produce a positive electrode. Then, a positive electrode lead was attached to the exposed aluminum foil part of the positive electrode.

[0149] As the positive electrode active material, in addition to the lithium cobalt oxide, various positive electrode active materials such as lithium nickel cobalt aluminum oxide (NCA) and lithium nickel cobalt manganese oxide (NCM) can also be used.

[0150] (Electrolyte production) An electrolyte solution was prepared by dissolving lithium hexafluorophosphate (LiPF6) as an electrolyte salt at a concentration of 1.0 mol / L in a solvent prepared by mixing ethylene carbonate (EC) and ethyl methyl carbonate (EMC) at a mass ratio of 5:5.

[0151] (Secondary battery manufacturing) Next, the positive electrode and the negative electrode produced above were attached to each other through a separator made of a microporous polyethylene film having a thickness of 25 μm. The positive electrode, the negative electrode, and the separator were wound in the longitudinal direction, and a protective tape was attached to the outermost periphery to produce a wound electrode body. Next, the wound electrode body was loaded between the exterior members, and the three sides of the exterior member corresponding to the outer periphery of the wound electrode body were heat-sealed. For the exterior member, a moisture-proof aluminum laminate film was used in which a 25 μm-thick nylon film, a 40 μm-thick aluminum foil, and a 30 μm-thick polypropylene film were laminated in this order from the outermost layer. Then, an electrolyte was injected from one open side of the exterior member, and the open side of the exterior member was heat-sealed under reduced pressure. A secondary battery was produced by the above process.

[0152] (Secondary Battery Design) The secondary battery was designed as follows. First, one-sided coated samples of the positive and negative electrodes were separately prepared, and coin cells with Li as the counter electrode were prepared for each of the positive and negative electrodes. Next, the coin cell with the positive and Li electrodes was charged at a constant current of 0.1C up to an initial charging voltage of 4.45V, and then the capacity was measured when the coin cell was charged at a constant voltage of 0.1C until the current value was 1 / 10 of the constant current value. In addition, the coin cell with the negative and Li electrodes was charged at a constant current of 0.1C up to an initial charging voltage of 0V, and then the capacity was measured when the coin cell was charged at a constant voltage of 0.1C until the current value was 1 / 10 of the constant current value.

[0153] The charge capacity per thickness of the positive and negative electrode mixtures was calculated, and the thicknesses of the positive and negative electrode active material layers were set using the calculated values ​​so that the ratio of the charge capacity of the positive electrode to the charge capacity of the negative electrode was 0.9. The thicknesses of the positive and negative electrode active material layers were adjusted by the solid content and coating speed of the positive and negative electrode mixture slurries.

[0154] (evaluation) The secondary battery prepared by the above steps was charged at a constant current of 0.2 C in an environment of 23° C. until the battery voltage reached 4.40 V, and then charged at a constant voltage of 4.40 V until the current value reached 0.025 C. The secondary battery was then discharged at a constant current of 0.2 C until the battery voltage reached 3.0 V (initial charge / discharge).

[0155] After the initial charge and discharge, the 2nd to 100th cycles of charge and discharge were repeated under the following conditions. Specifically, the secondary battery was charged at a constant current of 0.5C until the battery voltage reached 4.40V in an environment of 23°C, then charged at a constant voltage of 4.40V until the current value reached 0.025C, and then discharged at a constant current of 0.5C until the battery voltage reached 3.0V. These charge and discharge cycles were performed 100 times as one cycle. The cycle characteristics were calculated by dividing the discharge capacity at the 100th cycle by the discharge capacity at the 2nd cycle. Note that the battery characteristics are largely dependent on the amount of Si-based negative electrode active material, so in Table 1 below, the cycle characteristics are shown as relative values ​​when the comparative examples prepared for each amount of Si-based negative electrode active material are taken as 100.

[0156] The recovery rate was measured according to JIS6251 as follows. Specifically, each material was dried, punched out into a 20 μm thick dumbbell shape No. 8 (16 mm long at the center), and stretched to 100% (until the center length was 32 mm) using a tensile tester, after which the length of the center after stretching was measured. Based on the measurement results, the recovery rate was calculated using the following formula. Recovery rate (%) = (32 mm - length of center part after tension) / 16 mm x 100

[0157] Since it is difficult to stretch polyimide to 100%, the recovery rate was not measured.

[0158] The elastic modulus was measured using the nanoindentation method. The nanoindentation method is a measurement method in which a diamond indenter is pressed into the measurement object, and the load and displacement during pressing are measured to calculate mechanical properties such as the elastic modulus from the load-displacement curve. The nanoindentation method allows the elastic modulus of thin films to be measured with high accuracy. A nanoindenter is known as a device for performing the nanoindentation method. The nanoindenter is composed of a transducer and a controller that control the diamond indenter and detect the measured value, and a personal computer for operation.

[0159] Specifically, a solution of each material was applied to a substrate such as a silicon wafer using a spin coater so that the film would have a thickness of 1 μm after drying, and the elastic modulus was measured by pressing the applied thin film with a nanoindenter. A diamond indenter with a side length of 20 μm and a flat tip was used for pressing, and the elastic modulus was calculated from the load-displacement curve when the indentation depth was increased to 200 nm.

[0160] [Table 1]

[0161] Each entry in Table 1 represents the following materials. PU1: Polyurethane resin made from polyolefin polyol and polyisocyanate with an average molecular weight of 3000 PU2: Polyurethane resin made from polyolefin polyol and polyisocyanate with an average molecular weight of 10,000 PU3: Polyurethane resin made from polyolefin polyol and polyisocyanate with an average molecular weight of 50,000 PU4: Polyurethane resin made from polycarbonate-based polyol and polyisocyanate with an average molecular weight of 3000 PVDF: Polyvinylidene fluoride SPA: Sodium polyacrylate LPA: Lithium polyacrylate PAA: Polyacrylamide PI: Polyimide AR: Aramid SBR: Styrene butadiene rubber MWCNT: Multi-walled carbon nanotubes SWCNT: Single-wall carbon nanotube

[0162] As can be seen from the results shown in Table 1, the secondary batteries according to Examples 1 to 14 have higher cycle characteristics than the secondary batteries according to Comparative Examples 1 to 4.

[0163] It can be seen that the secondary batteries according to Examples 1 and 2 have higher cycle characteristics than the secondary batteries according to Comparative Examples 2 and 4 because an organic resin with a recovery rate of 70% or more is used as the covering material. This is because when the recovery rate of the organic resin contained in the covering material is low, the negative electrode active material layer does not return to its original state when the active material core contracts after expanding, and the negative electrode active material layer gradually expands as the charge / discharge cycle progresses, making it difficult for the Si-based negative electrode active materials to come into contact with each other, and gradually making it difficult to obtain capacity.

[0164] It is found that the secondary battery according to Example 1 has higher cycle characteristics than the secondary battery according to Comparative Example 3 because a material having a higher elastic modulus than the organic resin contained in the coating material is used as the negative electrode binder. This is because the use of a material having a higher elastic modulus than the organic resin contained in the coating material as the negative electrode binder increases the rigidity of the negative electrode active material layer as a whole, thereby making it possible to suppress expansion of the negative electrode active material layer as the charge-discharge cycle progresses.

[0165] It can be seen that the secondary batteries according to Examples 7 and 8 have higher cycle characteristics than the secondary battery according to Example 1 because a surface conductive agent is further used. This is because the surface conductive agent can strengthen the connection between the primary particles or secondary particles of the Si-based negative electrode active material, thereby suppressing the collapse of the Si-based negative electrode active material due to expansion and contraction, and more firmly maintaining the conductive network. In addition, the surface conductive agent can reduce the electrical resistance of the Si-based negative electrode active material increased by the coating material, thereby suppressing the deterioration of cycle characteristics due to the increase in resistance of the Si-based negative electrode active material.

[0166] It is also seen that the secondary battery according to Example 15 has higher cycle characteristics than the secondary battery according to Comparative Example 5, the secondary battery according to Example 16 has higher cycle characteristics than the secondary battery according to Comparative Example 6, and the secondary battery according to Example 17 has higher cycle characteristics than the secondary battery according to Comparative Example 7. That is, it is seen that the effect of the present technology can be similarly exhibited even when the ratio of the Si-based negative electrode active material to the carbon-based negative electrode active material is changed.

[0167] Although the present technology has been described above with reference to an embodiment and examples, the configuration of the technology is not limited to the configuration described in the embodiment and examples and can be modified in various ways.

[0168] Specifically, the element structure of the electronic element has been described as being of a wound type (wound electrode body), but the element structure of the battery element is not particularly limited, and may be of other element structures such as a stacked type (laminated electrode body) in which electrodes (positive and negative electrodes) are stacked, and a zigzag-folded type in which the electrodes (positive and negative electrodes) are folded.

[0169] Although the electrode reactant is lithium, the electrode reactant is not particularly limited. Specifically, the electrode reactant may be other alkali metals such as sodium and potassium, as described above, or alkaline earth metals such as beryllium, magnesium, and calcium. In addition, the electrode reactant may be other light metals such as aluminum.

[0170] The effects described in this specification are merely examples, and the effects of the present technology are not limited to the effects described in this specification. Therefore, other effects may be obtained with respect to the present technology.

Claims

1. The battery includes a positive electrode, a negative electrode including a Si-based negative electrode active material, a carbon-based negative electrode active material, a negative electrode binder, and a negative electrode conductive agent, and an electrolyte solution; The Si-based negative electrode active material includes an active material core including a Si-containing compound, and a coating material that coats at least a portion of a surface of the active material core, the elastic modulus of the negative electrode binder is higher than the elastic modulus of the covering material, The covering material has a tensile elongation of 100% or more, and a recovery rate of the covering material after a tensile elongation of 100% is 70% or more; a total ratio of the negative electrode binder to a total mass of the Si-based negative electrode active material, the carbon-based negative electrode active material, the negative electrode binder, and the negative electrode conductive agent is 4 mass% or more; Secondary battery.

2. The coating material is a polyurethane resin having an average molecular weight of 10,000 or less. The secondary battery according to claim 1 .

3. The polyurethane resin is a polymer of a polyolefin polyol and a polyisocyanate. The secondary battery according to claim 2 .

4. The negative electrode binder includes at least one of polyvinylidene fluoride, polyacrylate, polyimide, aramid, polyacrylamide, and styrene-butadiene rubber; The secondary battery according to claim 1 .

5. The Si-based negative electrode active material further includes a surface conductive agent that covers at least a portion of the surface of the active material core. The secondary battery according to claim 1 .

6. The negative electrode further includes a carbon-based negative electrode active material, The secondary battery according to claim 1 .

7. It is a lithium-ion secondary battery. The secondary battery according to claim 1 .

Citation Information

Patent Citations

  • Negative electrode for lithium ion secondary battery and lithium ion secondary battery using the same

    JP2017152123A

  • Electrode for nonaqueous electrolyte secondary battery

    JP2019071227A

  • Electrode material for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery electrode and non-aqueous electrolyte secondary battery using same

    WO2015053200A1

  • Secondary battery, battery pack, electric vehicle, electric tool and electronic device

    WO2018146865A1

  • Electrode for electricity storage devices and method for producing same

    WO2019044491A1